THE HIGH FEMALE AND HIGH MALE'S SIMILAR TALK STRATEGIES AMONG FEMALE TALK IN THE PATERNAL SOCIETY - Giyoto, Giyoto; Inderasari, Elen; Untari, Lilik (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
Islamic paternal parenting has socially patterned the man dominant language behavior over woman since childhood. This study explores the dominance distributions of high female and low female status in their informal talk strategy, the actual language use,  among the students of The State Islamic Institute of Surakarta in three functional topical units of conversations. The analysis technique was introduced by Sinclair and Coulthard (1975), for which Leech (1983) modifies the speech acts. The data implies that the talk strategy among Muslim females is relatively similar to that of males. The higher female controls and initiates the interaction more while the lower is softer, more polite, more mutually supportive, and more cooperative to whomever she speaks to regardless of the status.Muslim Female; Act; Move; Talk Strategy